2014
DOI: 10.3109/10826084.2013.852584
|View full text |Cite
|
Sign up to set email alerts
|

“PMA Sounds Fun”: Negotiating Drug Discourses Online

Abstract: In 2007, a young woman, Annabel Catt, died after consuming a capsule sold as 'ecstasy' that contained para-methoxyamphetamine (PMA). In this paper, we describe how this death was depicted in online drug-user communities and illustrate how the meanings of drug use are negotiated in online settings. News articles, public online discussions, and online fieldwork formed the data. This paper demonstrates how dominant drug discourses may be resisted by drug users, drawing on theories of health resistance and Kane Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
0
34
0
1
Order By: Relevance
“…However, publicly available discussions have at least two conceivable flip sides. First, Barratt et al [31] have revealed a less acknowledged and oppositional discourse to harm reduction which incorporates a desire for dangerous drug use and downplay of harm reduction. This alternative discourse was not revealed by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, publicly available discussions have at least two conceivable flip sides. First, Barratt et al [31] have revealed a less acknowledged and oppositional discourse to harm reduction which incorporates a desire for dangerous drug use and downplay of harm reduction. This alternative discourse was not revealed by the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents or people curious about drugs, the nature of this information is of interest because it has the potential to alter the drug use behaviour of those who obtain it (Norman, Grace, & Lloyd, 2013). Although publicity could entail an increase in drug use, online discussions can also be characterized by a concern for safety and harm reduction among drug users (Soussan & Kjellgren, 2014), and can be framed in a way that privileges the pleasures of getting high (Barratt, Allen & Lenton, 2014). This shows the importance of the Internet for access to userrelevant information about illegal drugs, and it displays the uniqueness of the market for new psychoactive substances, in which online networking sites seem to play a crucial part in marketing and raising awareness of new products (Griffiths et al, 2010).…”
Section: Online Communitiesmentioning
confidence: 99%
“…The study is intended to further academic and policy dialogue around online consumerism of drug discourses (Barratt et al, 2014;Race, 2009), which in this netnographic study observed the nostalgic interest in Laudanum preparation, habituation, and indigenous harm reduction dissemination among contemporary drug users. Development of targeted and credible "counterpublic" harm reduction initiatives situated within online consumerism of communal drug knowledge is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Netnographic studies increasingly identify the internet as hub of communal folk pharmacological knowledge exchange and cyber supported indigenous harm reduction between users and interested parties (Barratt, Allen, & Lenton, 2014;Van Hout, 2014b, 2014c, 2014dVan Hout & Bingham, 2013), despite prior research not recognizing the internet as significant source for diversion of opioids (Hamer, Spark, Wood, & Roberts, 2013;Inciardi, Surratt, Kurtz, & Cicero, 2007;Inciardi et al, 2009;Wilsey et al, 2010). Seeking of information on laudanum was underpinned by user reminiscing about Victorian availability and use of laudanum.…”
Section: Discussionmentioning
confidence: 97%